Total Absorption Spectroscopy of Fission Fragments Relevant for Reactor Physics and Nuclear Structure and Astrophysics - Estienne Magali; Guadilla V.; Fallot M.; Algora A.; Taín J. L.; Porta A.; Giot L.; Briz J. A.; Bui V. M.; Cormon S.; Jordan D.; Le Meur L.; et al. (EPJ Web of Conferences, 2023)
The accurate determination of reactor antineutrino spectra remains a very hot research topic, where new questions have emerged in recent years. Indeed, after the “reactor anomaly” – a deficit of measured antineutrinos at short baseline reactor experiments with respect to spectral predictions – the three international reactor neutrino experiments Double Chooz, Daya Bay and Reno have evidenced spectral distortions in their measurements with respect to the same spectral predictions. This puzzle is called the “shape anomaly”. Recently summation calculations of reactor antineutrino spectra based on the use of nuclear data have obtained the best agreement to date with the reactor neutrino flux measurements at the level of 2% thanks to a decade of Total Absorption Gamma-ray Spectroscopy (TAGS) measurements at the radioactive beam facility of the University of Jyväskylä in two experimental campaigns. A selection of the results obtained so far is presented.